Potentiating Effect of Platelets and Endothelial-Derived Extracellular Vesicles on the Coagulation Activity of Monocytes Stimulated with Antiphospholipid Antibodies (2025)
Antiphospholipid antibodies are autoantibodies that can lead to vascular thrombosis in vivo. It is known that aPLs bind and activate the vascular endothelium, triggering the release of large extracellular vesicles (lEVs). Some of the features of these vesicles, as well as whether they can propagate a procoagulant state by interacting with peripheral blood monocytes, are unknown. In this research, immunoglobulin G (IgG) from patients with APS was used to induce the release of lEVs in human umbilical vein endothelial cells, which were enriched and characterized by flow cytometry. The ability of these lEVs and activated platelets to enhance tissue factor expression and promote the procoagulant activity of peripheral blood monocytes was assessed by flow cytometry and a recalcified plasma-based assay. Our results showed that lEVs released by endothelial cells stimulated with IgG from APS patients (lEVAPS), compared with those released upon stimulation with IgG from control women (lEVC), more frequently exhibit ICAM-1 (CD54) on their surface (lEVC 720.7, lEVAPS 1262 CD54+ particles/μL, P < 0.05), and are opsonized by IgG (lEVC 28.5, lEVAPS 40.6%, P < 0.001). Although these traits suggest that lEVAPS can interact with monocytes through integrins and Fc receptors, thereby enhancing their tissue factor expression and procoagulant activity, this did not occur in our experimental setting. Platelets increased the procoagulant potential of monocytes regardless of the antibodies with which they were stimulated. In conclusion, aPLs trigger the release of lEVs displaying CD54 and IgG on their surface. The functional implications of these features require further exploration.